Microstructural analysis of germanium modified tin‐copper brazing filler metals for transient liquid phase bonding of aluminium: Mikrostrukturanalyse von Germanium‐modifizierten Zinn‐Kupfer Lotbändern für die transient liquid phase‐Bindung von Aluminium. Issue 12 (10th January 2018) - Iskandar, R.; Schwedt, A.; Mayer, J.; Rochala, P.; Wiesner, S.; Öte, M.; Bobzin, K.; Weirich, T.E.
Abstract: The present contribution summarises first results that have been achieved with the new brazing material Sn75Cu20Ge5 (wt‐%) for transient liquid phase (TLP) bonding of aluminium cast alloy AlSi7Mg0.3 (wt‐%). The microstructure of the braze ribbons and the obtained joints have been thoroughly investigated on different length‐scales using scanning and transmission electron microscopy as well. Whereas the braze ribbon material is only composed of beta‐tin, η‐phase (Cu6 Sn5 ) and some germanium rich precipitates, the transient liquid phase joint displays a much more complex microstructure that consist mainly of beta‐tin and different aluminium‐copper and aluminium‐germanium phases. In addition small silicon oxide rods and a hitherto unreported hexagonal aluminium‐copper‐magnesium‐germanium phase with approximated lattice parameters a  = 0.7123 nm, c  = 2.40 nm have been found in the seam of the joint.